2005
DOI: 10.1063/1.1868871
|View full text |Cite
|
Sign up to set email alerts
|

All-MgB2 tunnel junctions with aluminum nitride barriers

Abstract: All-MgB2 tunnel junctions were fabricated on a C-plane sapphire substrate. The current-voltage characteristics showed both quasiparticle and Josephson tunneling currents and a clear gap structure. The current density was 115A∕cm2 for a 20×20μm2 junction with a 0.14-nm-thick AlN layer, and the ratio of the subgap resistance and normal resistance was 3.3. The gap voltages of lower and upper MgB2 electrodes were estimated to be 2.2 and 1.5mV, respectively. The temperature dependence of the Josephson current indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 16 publications
4
58
1
2
Order By: Relevance
“…In comparison with the theoretical predictions 21 , the majority of the reports indicate depressed values of such product and different temperature behaviors irrespectively to the weak link or tunnel nature of the junctions 12,14,26,28,29 . To the best of our knowledge, in the majority of the cases coupling of the conventional superconductor with only the 3D band of the multi-gap material is inferred.…”
Section: Nb Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the theoretical predictions 21 , the majority of the reports indicate depressed values of such product and different temperature behaviors irrespectively to the weak link or tunnel nature of the junctions 12,14,26,28,29 . To the best of our knowledge, in the majority of the cases coupling of the conventional superconductor with only the 3D band of the multi-gap material is inferred.…”
Section: Nb Cmentioning
confidence: 99%
“…In the experiments, however, effective Josephson coupling of the 2D band σ with a 3D band, both of a MgB 2 or of a conventional superconducting counterelectrode, has been not observed. In addition to this, the measured I C R N values are often severely depressed and regardless to the junction orientation, different temperature dependencies of the Josephson current are often reported 12,14,26,27,28,29 . Similar behavior is expected in proximity coupled S-I-N-S structures 30 , and in MgB 2 junctions it has been attributed to degradation of T C at the interface and/or to the barrier nature and quality.…”
Section: Introductionmentioning
confidence: 99%
“…All-MgB 2 weak-link junctions [9][10][11][12][13] are not ideal for integrated circuits. All-MgB 2 sandwich-type Josephson junctions have been reported, [14][15][16] some with near-ideal Fraunhofer patterns, however, the J c values are very low and drop quickly to zero at 20-25 K. In this letter, we report MgB 2 / MgO/ MgB 2 sandwich-type Josephson junctions with high J c up to 275 kA/ cm 2 at 4 K, which remains nonzero up to 40 K. The ultimate speed limit of Josephson junction-based rapid single flux quantum ͑RSFQ͒ circuits is proportional to the product I c R n , where I c is the critical current and R n the resistance of the junction in the normal state.…”
mentioning
confidence: 99%
“…3 Several groups have already demonstrated tunnel junctions with both lower T c superconductors [4][5][6][7] and with MgB 2 as the top electrode [8][9][10] using different barrier layers such as AlN, MgO, Al 2 O 3 , and the thermal oxide. The results indicate that key issues for fabricating tunnel junctions are the uniform coverage of the base electrode by these barriers, as well as the stability of these barriers when the top MgB 2 electrode is deposited at temperatures ≥300 o C. In junctions with AlN barriers 9 the data suggested that a thermal oxide must be part of the barrier, and that stimulated our work. The utility of the native oxide is well known in the popular Nb/Al-Al oxide/Nb trilayer junction technology.…”
mentioning
confidence: 99%